Tubo-ovarain abscess in patient with ovarian endometriosis - Gupta, Monika; Jain, Tripti; Goel, Neha; Singh, Sunita (International Journal of Research in Medical Sciences, 2023)
Tubo-ovarian abscess (TOA) is a sequela of pelvic inflammatory disease (PID) found in 15-34% of patients, is comprised of an infectious, inflammatory complex encompassing the fallopian tube and ovary. We are presenting a case of TOA with endometriosis in a patient who underwent total abdominal hysterectomy and bilateral salpingo-oophorectomy. Histopathological findings were compatible with endometriosis with xanthogranulomatous salpingitis and oophoritis. In our patient there was no history of any chronic infection, gynecological procedures or intra uterine device and single partner. The purpose of this case is to make aware of this condition and requirement of further studies to investigate the risk of TOA in patients with endometriosis to find out the exact cause to prevent unnecessary surgery at later stage.